Globalization is Good or Bad? Considering View of Next Generation Leaders - Chowdhury, Iftekhar Amin; Suki, Norazah Mohd (Richtmann Publishing, 2012)
Globalization has the effect on world business in this 21st century undoubtedly. Effects come through both positive andnegative (dark) sides. This study aims to examine how future business leaders view globalization. 494 samples involved andwere selected via nonrandom convenient sampling process. Results infer that business majors have a different attitude towardglobalization compared with non-business majors. Next, studentsâ€™ attitude toward globalization is also likely to be influenced bytheir family background, especially their parentsâ€™ occupations. Ultimately, business environments are going global, internalenvironments, including the mind-set of future managers, may change toward more globalization, resulting in potentially moreglobally oriented strategies. Managers need to be on guard against antiglobalization sentiments tendency experienced by largesegments of the population for more â€œcreeping globalization.â€